RELATIONSHIP BETWEEN LINGUISTICS INTELLIGENCE TO LOGICAL-MATHEMATIC INTELLIGENCE IN PUBLIC ELEMENTARY SCHOOL STUDENTS KELURAHAN CIJANTUNG, EAST JAKARTA - Priarti Megawanti; Eka Septiani (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Abstract: For those who studied ang studying mathematics, are often labeled with a tendency to be stiff and few words, less creative, even minus the imaginative. In fact, someone who is great in numbers actually able to understand the nature and can solve the daily problems. That is because mathematics is actually more than just the science of counting numbers and memorizing formulas, but the science that simplifies the universe into numbers and formulas. The ability to solve mathematical problems cannot be separated from language skills. Language skills will help someone to understand mathematical language that uses a combination of numbers, letters, and symbols. That way, it is very interesting to know whether language ability has a relationship with one's mathematical ability. Simple linear regression test showed that there is a significant influence between language intelligence and mathematical intelligence. The results of the analysis for simple correlation (Product Moment) showed a significant positive correlation between language intelligence and mathematical intelligence. The coefficient of determination is obtained at 44.021%, which means that Language Intelligence affects Mathematical Intelligence as much as 44, 021%. Students who have language intelligence will more easily understand mathematical problems, because in answering a mathematical problem, one must be able to know the purpose of the problem first. Because mathematics uses a combination of numbers, letters, and symbols, it is very important for someone who wants to master mathematics to understand the meaning and purpose of language. Logically, someone who has language intelligence has a curiosity to find out the implicit meaning of what he is learning. He tends not only to memorize the formula but try to understand it. At the stage of being able to understand a language, someone will more easily understand the purpose of the problem and answer it correctly.Key Words: intelligence, language, mathematical.